(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Kashyapa Samhita is an ancient text having many benchmark contributions in the field of Kaumarbhritya. Lehaadhya is a major contribution of Kashyapa Samhita where Lehana Yoga (lickable-semisold forms of herbs) is given. Lehana are most palatable and easy to prepare yoga for pediatric practice. In this article i have presented my views on how a practitioner can utilize drug combination of Lehaadhya in day to day practices. Various combinations given in Lehadhyaya are mainly given as preventive measures. But if we think on indication of Lehana, and side by side we thought on pediatric cases we encounter in day to day practices, we can realize that Lehana combinations are also useful in many common ailments in children. In other words Lehana combinations are not just for Preventive purpose and enhancing immunity and intellectual purpose but also can be used in so many common ailment found in pediatric practices. The thing we should kept in mind while using Lehana is its contraindications. Once we are clear about where we should not use Lehana and directly move on the treatment of particular disease, it becomes much easier to decide in which cases Lehana can be used.